Naples, China and the Cosmos: the theology of an eighteenth-century Chinese priest - Harrison, H (Cambridge University Press, 2023)
This paper examines the correspondence of Li Zibiao (1760-1826), a Chinese Catholic priest who was trained in Naples and then worked as a missionary in north China. Whereas existing studies of Chinese theology mainly focus on accommodation and enculturation, Li responded to the persecutions he lived through by thinking in global terms and de-emphasizing differences between Europe and China. This enabled him to use developments in casuistry and the moral theology associated with Alphonso de Liguori to avoid the strictures of the Chinese Rites Controversy. Li’s ideas thus suggest some of the roots of north China’s resilient rural Catholicism.